Adoption of sustainable retrofit in UK social housing 2010-2015. Issue 5 (13th November 2017) - Swan, William; Fitton, Richard; Smith, Luke; Abbott, Carl; Smith, Liz
Abstract : Purpose: The Retrofit State of the Nation Survey has tracked the perceptions of social housing sector professionals' views of retrofit since 2010. It has taken the form of three surveys conducted in 2010, 2013 and 2015. Here, the authors bring together the three surveys to specifically address the adoption and perceived effectiveness of retrofit technology in social housing projects. The purpose of this paper is to identify the changing perceptions of social housing professionals over a period of significant policy change within in the sector. Design/methodology/approach: The research takes the form of a cross-sectional attitudinal, self-completion survey, covering sections considering the adoption levels and perceived effectiveness of different retrofit technologies. The target sample was medium to larger scale registered social housing providers. The surveys were conducted in 2010, 2013 and 2015. Findings: In terms of effectiveness, the reliance on tried and tested technologies is apparent. Emerging or more complex technologies have declined in perceived effectiveness over the period. It is clear that social housing has adopted a wide range of technologies, and the larger providers, with whom this survey is undertaken, potentially represent a significant pool of UK retrofit experience. Originality/value: The survey provides a record of the changing attitudes of social housing providers to specific technologies over the period of 2010-2015, which has seen significant changes in the energy and social housing policy. The findings show the link between policy instruments and adoption, with policy instruments mapping to adoption in the sector. Perceived effectiveness reflects a preference for more established technologies, an issue that is highlighted in the recent Bonfield Review.